2017
DOI: 10.1016/j.cyto.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Age predicts cytokine kinetics and innate immune cell activation following intranasal delivery of IFNγ and GM-CSF in a mouse model of RSV infection

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infections in young children and is further associated with increased healthcare utilization and cost of care in the first years of life. Severe RSV disease during infancy has also been linked to the later development of allergic asthma, yet there remains no licensed RSV vaccine or treatment. Pre-clinical and clinical studies have shown that disease severity and development of allergic asthma are associated with differences in cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, it has been demonstrated that IFN γ production during neonatal infection influences the outcome of RSV pathology upon adult reinfection [ 109 ]. Indeed, it has been shown that intranasal injection of recombinant IFN γ in neonatal RSV-infected mice induces a better AM activation characterized by the expression of CAM markers (CD86 + , MHC II + and CCR7 + , and mannose receptor − ) on neonatal AMs and reduced viral load in the lungs [ 90 , 95 , 110 ].…”
Section: Experimental Strategies To Modulate the Neonatal Susceptimentioning
confidence: 99%
“…Furthermore, it has been demonstrated that IFN γ production during neonatal infection influences the outcome of RSV pathology upon adult reinfection [ 109 ]. Indeed, it has been shown that intranasal injection of recombinant IFN γ in neonatal RSV-infected mice induces a better AM activation characterized by the expression of CAM markers (CD86 + , MHC II + and CCR7 + , and mannose receptor − ) on neonatal AMs and reduced viral load in the lungs [ 90 , 95 , 110 ].…”
Section: Experimental Strategies To Modulate the Neonatal Susceptimentioning
confidence: 99%
“…In xenograft, mouse models have verified that age is connected with changes in immune system [11, 12]. When compared with younger ones, older mice further proved modificative cytokine kinetics [13] and reduced CD8 + T cell proliferation [14], and this is also associated with the decrement in T cell function [15] and CD28 expression [16, 17], which is a co-stimulatory signal for T cell activation [18]. But in clinical trials, Elias et al [19] reviewed efficacy and safety of ICI in patients with non-small cell lung cancer, melanoma, and renal cancer and found that there were no obvious age-associated difference in overall survival (OS) and side effects among those older and younger patients.…”
Section: Introductionmentioning
confidence: 99%
“… The data presented here are related to the research article entitled “Age predicts cytokine kinetics and innate immune cell activation following intranasal delivery of IFNγ and GM-CSF in a mouse model of RSV infection” (Eichinger et al, 2017) [1] . The cited manuscript demonstrated that the macrophage-stimulating cytokine, interferon gamma (IFNγ), but not granulocyte macrophage-colony stimulating factor (GM-CSF), effectively enhanced viral clearance in infant mice infected with respiratory syncytial virus (RSV) following intranasal delivery.…”
mentioning
confidence: 99%